Imaging Wales : Contemporary Art in Context - Adams, Hugh (Cardiff : Seren Wales Arts International, 2003)
IMAGING WALES is a concise and richly illustrated insight into the lively visual arts scene in Wales.
Ayoagi, Reiko ; Bala, Iwan ; Brown, Christopher ; Burns, Brendan ; Cooper, Andrew ; Cox, Richard ; Cushway, David ; Davies, Ivor ; Davies, Tim ; Elias, Ken ; Evans, Cerith Wyn ; Fenoulhet, Simon ; Fielding, Kim ; Finnemore, Peter ; Garner, David ; Harris, Richard ; Hastie, David ; Howells, Neale ; Ingham, Karen ; Jones, Glyn ; Jones, Huw ; Lawrence, Philippa ; Lloyd Jones, Mary ; Long, Tim ; MacKinnon-Day, Patricia ; Meirion Morris, John ; Mitchell, Simon ; Nash, David ; Nicol, Philip ; Pearce Jones, Angharad ; Rees, Marc ; Rees, Sara ; Rhys James, Shani ; Seawright, Paul ; Setch, Terry ; Shapland, Anthony ; Stitt, Andre ; Webster, Catrin ; Williams, Lois ; Williams, Sue ; Wood, Craig
Critic Hugh Adams provides an informative, historic and social context for the dynamic selection of artists and institutions that are profiled in this new publication. Imaging Wales gives a flavour of the diversity of visual arts practice explored by new and established artists. Installation, sculpture, photography, performance, painting, mixed media and video are among the artforms represented in the book.
More than forty artists are featured and include David Nash, Shani Rhys James, André Stitt, Mary Lloyd Jones, Tim Davies, Sara Rees, Peter Finnemore, and Venice Biennale selected artists Cerith Wyn Evans and Paul Seawright.
Engels
boek
Keywords: Wales; Engeland